Disponibilidade de fósforo em solo tratado com resíduos urbanos e industriais sob sistema de plantio direto cultivado com soja - Santos, Susiane de Moura Cardoso dos [UNESP] (2014)
Industrial and municipal wastes applied to agricultural crops under no-tillage (NT) can promote benefits in physical, chemical and biological soil properties. The reuse of these materials reduces the supply of synthetic fertilizers, providing greater economic and environmental sustainability. Apart from acting as attenuators of soil acidity, some of these residues are excellent sources of plant nutrients such as phosphorus (P). Understanding the dynamics of P arising from waste and applied in tropical soils is important to assist in fertilization management of agricultural species. In this context, the objective of this study was to analyze the chemical changes in the soil, mainly through the fractionation of P, and to assess the nutritional status and grain yield of soybean plants grown under no-tillage (NT) in an Oxisol that received application of municipal and industrial waste. The experimental design was randomized blocks, 4x3+2 factorial scheme with three replications. Treatments were four residues LC - centrifuged sewage sludge with addition of quicklime (CaO); LB - sewage sludge from the digester with the addition of polyelectrolytes; and - steel slag; and LCAL - lime slurry applied at dosages of 0, 2, 4 and 8 mg ha-1. In soil sample collected in the 0-5, 5-10, 10-20 and 20-40 cm depth was held fractionation of soil P (RTA Pi, Pi Po and NaOH 0.1 mol L-1, HCl Pi, Pi Po and NaOH 0.5 mol L-1, residual P) and evaluated some characteristics of soil pH, organic matter, V%, P, Ca and Mg. In the plant, we assessed the nutritional status, through the determination of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, and Zn in the leaves and grain yield. It was found that the application of the waste, along with the annual planting fertilization, contributed to a significant increase and preferred organic forms of phosphorus in the soil, and the LB and ...